The Absence of Fatherhood from William Bloom as Reflected in Daniel Wallace’s Big Fish: A Study of Masculinism - Putri, Rifqi Amri (Universitas Gunadarma, 2016)
The conflict of disagreement between parents and children is a common issue. In the real life, this disturbance in family relationship can be found in daily life. One of them is the absence of fatherhood in family. William Bloom tries to figure out who his father really is as a person. His father, Edward Bloom was always telling tall tales of his life and events that happened to him, clearly describing his life as completely extraordinary. In this undergraduate thesis the writer used masculinism theories from Kimmel’s, conceptual father involvement from Lamb’s et al and the absence of fatherhood from McLanahan’s. The writer wants to find out the factors causing the absence of fatherhood, in what way Edward Bloom involve fatherhood figure and masculinity sees the fatherhood as reflected in the novel entitled Big Fish: A Novel of Mythic Proportions. The writer used qualitative method to interpret phenomenon the absence of fatherhood in the novel, and as a problem of masculinity through the narrations and dialogues of Edward Bloom and William Bloom. The results are the factors causing the absence of fatherhood are labor and searching for identity. Edward Bloom was a good father in the beginning, but slowly became a shadowy figure to his son because there is no accessibility or available element of fathering involvement. The last, Edward bloom is an ideal man, because he involves the three dominants of manhood ideal: the genteel patriarch, the heroic artisan and the self-made man. However, the presence of fatherhood is really important in family and masculinity which is also represented as fatherhood figure and man identity. After that William finally learns how he is able to get to bottom of the truth and finds a way of truly understanding his father.Keywords: Fatherhoods, Masculinism, Big Fish.